Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas; Martin, Kent L. (My University, 2009)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2009_10
Keywords: MF648; Economics; Crops; MF